2012
DOI: 10.1080/09291016.2011.632231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cortisol and rectal temperature circadian rhythms in horses: the role of light/dark cycle and constant darkness

Abstract: To investigate the daily rhythm of cortisol in horse and to establish whether this rhythm is endogenously generated, we assessed serum cortisol concentrations in five clinically healthy Italian Saddle horses housed in individual boxes under natural light/dark (L/D) cycle followed by constant darkness, and we compared our results with the good established body temperature circadian rhythm. Blood samples and rectal temperature were collected every 3 h during all the experimental period. Two-way for repeated meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Horses that live in undisturbed natural habitats and trained horses, which have adapted to their environment, show a normal oscillation in CORT blood concentrations. These concentrations are generally higher in the morning and decrease throughout the day [45,46]. These same authors have reported maximum levels between 6:00 and 10:00 am and minimum between 6:00 and 9:00 pm.…”
Section: Circadian and Ultradian Rhythmsmentioning
confidence: 74%
“…Horses that live in undisturbed natural habitats and trained horses, which have adapted to their environment, show a normal oscillation in CORT blood concentrations. These concentrations are generally higher in the morning and decrease throughout the day [45,46]. These same authors have reported maximum levels between 6:00 and 10:00 am and minimum between 6:00 and 9:00 pm.…”
Section: Circadian and Ultradian Rhythmsmentioning
confidence: 74%
“…The post-workday samples were collected around 11:30 to 12:30 or 16:30 to 17:30h, to be compared with the samples before exercise, which were taken at 17:30 to 18:30h the previous day. Thus, all blood samples were collected out of the period of plasma cortisol concentration peak, which occurs early in the morning [28].…”
Section: Data Collectionmentioning
confidence: 99%
“…Daily rhythmicity of body temperature, cortisol and locomotor activity has been widely studied and described in many domestic animals, using different approaches, including diurnal index, conisor analysis and analysis of variance (Becker et al, 1985; BohĂĄk et al, 2013; De Jong et al, 2000; Fulkerson, Sawyer & Gow, 1980; Giannetto et al, 2012; Martin et al, 2010; Piccione et al, 2010; Piccione et al, 2011; Piccione, Caola & Refinetti, 2002; Piccione et al, 2008b; Refinetti & Piccione, 2005; Thun et al, 1981). Disruption of daily rhythmicity can be associated with health problems, reduced life expectancy and altered well-being of the organism (Froy, 2011; Vitaterna, Takahashi & Turek, 2001).…”
Section: Introductionmentioning
confidence: 99%